MACROZOOBENTHOS COMMUNITY STRUCTURE IN SETAN ISLAND, MANDEH TOURISM AREA, PESISIR SELATAN, WEST SUMATRA - Al-Izhar, Muhammad; Tanjung, Afrizal; Elizal, Elizal (Asian Journal of Aquatic Sciences, 2023)
Macrozoobenthos are aquatic organisms that live on the bottom of the water. Macrozoobenthos can be tolerant or sensitive to environmental changes. Organisms that live relatively sedentary and have varying adaptability to environmental conditions. However, there is no information about macrozoobenthos on Setan Island in Mandeh Tourism Area. To know/understand information about the density and distribution patterns of macrozoobenthos on Setan Island, this study was conducted in January 2022. The sampling area is in the intertidal zone of Setan Island. Sampling was conducted at three stations, each station was divided into three transects. Macrozoobenthos sampling was done using a sieve measuring 1mm x 1mm. The movement of macrozoobenthos to the gravel substrate was relatively slow to avoid the waves. Macrozoobenthos samples were then identified. The density of macrozoobenthos on Setan Island ranged from 2.89-3.89 ind/m2. Station 2 has a higher macrozoobenthos density of 3.89 Ind/m2, the calculation of macrozoobenthos on Setan Island obtained data on the distribution pattern of macrozoobenthos in clusters.